1998
DOI: 10.1083/jcb.141.6.1423
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Reactive Oxygen Species Production during Programmed Cell Death

Abstract: Reactive oxygen species (ROS) are thought to be involved in many forms of programmed cell death. The role of ROS in cell death caused by oxidative glutamate toxicity was studied in an immortalized mouse hippocampal cell line (HT22). The causal relationship between ROS production and glutathione (GSH) levels, gene expression, caspase activity, and cytosolic Ca2+ concentration was examined. An initial 5–10-fold increase in ROS after glutamate addition is temporally correlated with GSH depletion. This early incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
536
4
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 679 publications
(584 citation statements)
references
References 60 publications
29
536
4
3
Order By: Relevance
“…It has been documented that electron transport through the MRC is accompanied by the generation of various kinds of free radicals. 23,24 Overproduction of reactive oxygen species (ROS), the by-product of the MRC, causes cell death. 25 We examined whether overproduction of ROS by upregulation of MRC results in apoptosis upon treatment with IFN-b/RA.…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented that electron transport through the MRC is accompanied by the generation of various kinds of free radicals. 23,24 Overproduction of reactive oxygen species (ROS), the by-product of the MRC, causes cell death. 25 We examined whether overproduction of ROS by upregulation of MRC results in apoptosis upon treatment with IFN-b/RA.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are involved in cell survival and play a central role in apoptotic cell death signaling through the control of cellular energy metabolism, the generation of reactive oxygen species (ROS), and the release of apoptotic factors into the cytosol. Evidence showed that ROS are involved in the apoptotic mechanism of rotenone-mediated neurotoxicity [23] . The mitochondrial membrane permeability transition induces the formation of ROS by the inhibition of the respiratory chain and vice versa [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Prdx6 þ / þ LECs were resistant to identical oxidative stress, demonstrating an antioxidant role of PRDX6. Various reports show that higher levels of ROS are a common signal in different cell death pathways, and indicate a complex relationship between ROS levels and cell death, [48][49][50] in view of the finding that PRDX6-depleted cells bear higher levels of ROS, and are thereby more susceptible to oxidative stress.…”
Section: Phenotypic Changes In Prdx6 à/à Lecs Resemble Tgfb-induced Cmentioning
confidence: 99%